Pre‐adapting parasitic phages to a pathogen leads to increased pathogen clearance and lowered resistance evolution with Pseudomonas aeruginosa cystic fibrosis bacterial isolates. (9th November 2015) - Friman, V‐P.; Soanes‐Brown, D.; Sierocinski, P.; Molin, S.; Johansen, H. K.; Merabishvili, M.; Pirnay, J‐P.; De Vos, D.; Buckling, A.
Abstract: Recent years have seen renewed interest in phage therapy – the use of viruses to specifically kill disease‐causing bacteria – because of the alarming rise in antibiotic resistance. However, a major limitation of phage therapy is the ease at with bacteria can evolve resistance to phages. Here, we determined whether in vitro experimental coevolution can increase the efficiency of phage therapy by limiting the resistance evolution of intermittent and chronic cystic fibrosis Pseudomonas aeruginosa lung isolates to four different phages. We first pre‐adapted all phage strains against all bacterial strains and then compared the efficacy of pre‐adapted and nonadapted phages against ancestral bacterial strains. We found that evolved phages were more efficient in reducing bacterial densities than ancestral phages. This was primarily because only 50% of bacterial strains were able to evolve resistance to evolved phages, whereas all bacteria were able to evolve some level of resistance to ancestral phages. Although the rate of resistance evolution did not differ between intermittent and chronic isolates, it incurred a relatively higher growth cost for chronic isolates when measured in the absence of phages. This is likely to explain why evolved phages were more effective in reducing the densities of chronic isolates. Our data show that pathogen genotypes respond differently to phage pre‐adaptation, and as a result, phage therapies might need to be individually adjusted for different patients.